Effects of Varying Concentrations of Copper Sulfate on the Population Density of Chlorella SP. Nitzschia SP. and Oscillatoria SP. - Antone, Merab S. (Silliman Journal, 2024)
The effects of varying concentrations of copper sulfate (CuSOqg) on the population density of the algae Chlorella sp., Nitzschia sp. and Oscillatoria sp. were studied. CuSOg was applied to the algal cultures grown in the laboratory at ordinary room conditions. The growth rates of Chlorella sp. and Nitzschia sp. were greatly reduced at concentrations 0.1 ppm. Oscillatoria sp. was more sensitive to CuSOg, showing a significant reduction of growth at 0.05 ppm. Good logarithmic growth baad all sii species was observed in the controls.